2017
DOI: 10.1038/s41598-017-09393-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel molecular signatures of IgA nephropathy through an integrative -omics analysis

Abstract: IgA nephropathy (IgAN) is the most prevalent among primary glomerular diseases worldwide. Although our understanding of IgAN has advanced significantly, its underlying biology and potential drug targets are still unexplored. We investigated a combinatorial approach for the analysis of IgAN-relevant -omics data, aiming at identification of novel molecular signatures of the disease. Nine published urinary proteomics datasets were collected and the reported differentially expressed proteins in IgAN vs. healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 96 publications
2
10
0
Order By: Relevance
“…More generic profiling of blood proteins and peptides can provide biomarkers and molecular signatures. One study analyzed nine published urinary proteomics datasets and integrated them with transcriptomic data and literature knowledge to identify twenty proteins involved in IgAN in the kidney [22]. The relevance of three of these proteins (adenylcyclase-associated protein 1 (CAP1), SHCtransforming protein 1 (SHC1), and prolylcarboxypeptidase (PRCP)) was experimentally confirmed [22].…”
Section: Omics Datamentioning
confidence: 99%
See 1 more Smart Citation
“…More generic profiling of blood proteins and peptides can provide biomarkers and molecular signatures. One study analyzed nine published urinary proteomics datasets and integrated them with transcriptomic data and literature knowledge to identify twenty proteins involved in IgAN in the kidney [22]. The relevance of three of these proteins (adenylcyclase-associated protein 1 (CAP1), SHCtransforming protein 1 (SHC1), and prolylcarboxypeptidase (PRCP)) was experimentally confirmed [22].…”
Section: Omics Datamentioning
confidence: 99%
“…One study analyzed nine published urinary proteomics datasets and integrated them with transcriptomic data and literature knowledge to identify twenty proteins involved in IgAN in the kidney [22]. The relevance of three of these proteins (adenylcyclase-associated protein 1 (CAP1), SHCtransforming protein 1 (SHC1), and prolylcarboxypeptidase (PRCP)) was experimentally confirmed [22]. Finally, proteomics, like transcriptomics, is becoming increasingly available with spatial resolution from tissues [12], paving the way to generate multiplexed-histological data to complement classic pathological assessment.…”
Section: Omics Datamentioning
confidence: 99%
“…Krochmal and colleagues compared urinary peptide profiles of patients with and without CKD ( n = 121 and n = 118). [ 71 ] 302 differentially expressed peptides (adjusted p < 0.05) were analyzed with Proteasix. Activity of the predicted proteases was estimated based on the change in abundance of the investigated peptides.…”
Section: Technical Considerations and Biological Interpretation Of Fimentioning
confidence: 99%
“…In a subsequent study Krochmal and colleagues employed similar approaches to identify proteases potentially relevant in IgA nephropathy. [ 71 ] Combining the results with data from other public repositories allowed identifying 20 highly significant pathways. From these, three proteins predicted to be functionally relevant, adenylyl cyclase‐associated protein 1, SHC‐transforming protein 1, and prolylcarboxypeptidase were further verified by immunohistochemistry.…”
Section: Technical Considerations and Biological Interpretation Of Fimentioning
confidence: 99%
“…Among 232 proteins, 20 pathways were associated with IgAN consisting of 657 proteins for further analysis. They found 20 proteins with the highest relevance to disease pathology and finally validated 3 proteins which were the most important ones (including adenylyl cyclase-associated protein 1 [CAP1], prolylcarboxypeptidase [PRCP], and SHC-transforming protein 1 [SHC1]) by immunostaining of kidney tissue sections [108]. Gene ontology analysis showed that, a substantial part of significant proteins are involved in platelet activation processes, signaling and aggregation, which are all important in IgA pathology.…”
Section: Introductionmentioning
confidence: 99%